Managing Trade Policy During the Economic Crisis - Saez, Sebastian (World Bank, Washington, DC, 2012)
The global economic crisis has triggered rapid responses by governments worldwide to counteract its domestic effects, through fiscal stimulus packages, expansionary monetary policies, and financial bailouts. Ad hoc trade policy measures are increasingly being put in place. All countries share the responsibility of preserving a stable and predictable trade policy environment. To this end, trade policies must contribute to maintaining an open trading system consistent with World Trade Organization (WTO) principles. With the sharp decline in global merchandise trade volumes, expected to fall by 9 percent in 2009, countries have resorted to an array of measures to counter the detrimental effects of the crisis on their respective economies. Because this decline is a consequence of a deterioration of global demand, trade measures are not an effective response to this problem. On the contrary, policies that contribute to an open and stable trading system are the best policy option for the world community, especially in the current context.